ANALISIS SISTEM INFORMASI AKUNTANSI PENDAPATAN (Studi Kasus Pada PT. Maxindo Karya Selaras Bengkulu) - Herlin, Herlin; Zahara, Nani Halima; Yanti, Sepri (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2018)
Herlin, Nani Halima Zahara, Sepri Yanti; The purpose of this study was to determine the application of the accounting information system of income at PT. Maxindo Karya Selaras Bengkulu City. The analytical method used was the comparative method.The results showed that in the application of accounting information system of income at PT. Maxindo Karya Selaras Bengkulu City suitability reception system revenue, related functions, which are used documents , accounting records are used, and the network system procedures receipt of revenue by Mulyadi theory . Because at PT . Maxindo Karya Selaras Bengkulu City there is a process of income starting from coal orders from buyers, shipping and billing is already well underway.Key Words: Accounting Information System, Revenue.